Additive Effect of Fetal Magnetic Resonance Imaging to Prenatal Ultrasonography in Fetal Congenital Anomalies - Kirtis, Emine; Alkan Bulbul, Gul; Kandemir, Hulya; Sanhal, Cem Yasar; Karaali, Kamil; Mendilcioglu, Ibrahim Inanc (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVES: In this study, we aimed to assess the diagnostic accuracy of prenatal Ultrasonography (USG) and Magnetic Resonance Imaging (MRI) in fetal congenital anomalies. STUDY DESIGN: A retrospective cross-sectional analysis was conducted on 148 patients who had previously undergone prenatal MRI between January 2013 and May 2023. A total of 185 anomalies in 148 fetuses were evaluated using USG and MRI. The prenatal diagnoses were compared with definitive diagnoses and were classified as diagnosed, partially correct, questionable, or undiagnosed. In addition, USG and MRI findings were compared in terms of their consistency and consolidation. RESULTS: The postnatal evaluation revealed a total of 185 anomalies in 148 fetuses. USG diagnosed 94% of these anomalies, while MRI diagnosed 95.1% of them. Both USG and fetal MRI were able to diagnose 91.9% (n=170) of anomalies during the prenatal period. Fetal MRI provided an additional contribution to USG in the diagnosis of six anomalies (3.24%). CONCLUSION: In fetuses undergoing detailed ultrasonography and specialized neurosonography by experienced professionals, additional fetal anomalies exclusively detected through MRI are now found to be lower than previously documented. However, fetal MRI is presently employed to offer supplementary information, and advice, and assist in clinical decision-making. In the future, extensive prospective studies with standardized protocols for ultrasound imaging of the fetal brain are necessary to better understand the true role of fetal MRI in cases where fetal neurosonography has already been performed.